Effect Substitution Levell Fish Powder With Maggot Powder On Growth of Baung (Mystus nemurus CV) - Operiman Hulu; Indra Suharman; Adelina ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted in Experimental Pond of Fisheries and Marine Science Faculty of Riau University Pekanbaru, from May 2013 until June 2013. This study was performed to know the effect substitution level fish powder with maggot powder on growth of Baung (Mystus nemurus CV). Method used in this research was experimental method. Design used in this research was Complete Random Device (CRD) with five treatments and three replications. The treatment was: A) fish powder 100%, maggot powder 0%, B) fish powder 75%, maggot powder 25%, C) fish powder 50%, maggot powder 50%, D) fish powder 25%, maggot powder 75%, E) fish powder 0%, maggot powder 100%. The result showed that effect substitution levell fish powder with maggot powder on growth of Baung (Mystus nemurus CV) not significantly P > 0,05 to daily growth rate and efficiency food. Treatment with fish powder 100%, maggot powder 0% yield, the best daily growth rate 4,88% and efficiency food 12,98%.Keywords: Maggot powder, Fish powder, Baung (Mystus nemurus CV).